Konsep Pertanggung Jawaban Pidana Terhadap Pelaku, Pembantu, Dan Penganjur Dalam Jarimah Pembunuhan Menurut Qanun Aceh Nomor 6 Tahun 2014 - Farhan Mardiansyah; Ghina Sabrina; Deden Najmudin (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Murder is one of the most serious crimes in Islamic criminal law and receives special attention in Aceh Qanun Number 6 of 2014 concerning Jinayat Law. However, despite the existence of regulations, the concept of criminal responsibility for the principal perpetrator, accomplices, and instigators in murder remains unclear. At the das sein level, law enforcement practices demonstrate that authorities often have difficulty distinguishing the boundaries of involvement between perpetrator, accomplice, and instigator, particularly when the roles are indirect, hidden, or merely verbal. This results in inconsistencies in the imposition of ’uqubat and uncertainty for the parties involved. On the other hand, at the das sollen level, the Jinayat Qanun has normatively regulated the forms of criminal responsibility, including the principles of intent (qasd) and complicity (musyarakah), but these regulations have not provided operational explanations regarding their application in cases of murder with multiple participation. This is where an analytical gap emerges: there has been no specific study examining how the criminal liability norms in the Qanun Jinayat should be applied to properly separate the roles of perpetrator, accomplice, and instigator in murder. This study aims to fill this gap by analyzing the synchronization between the normative provisions of the Qanun Jinayat and the actual conditions in law enforcement, thereby formulating a clearer, more measurable, and consistent understanding of criminal liability for all parties involved in murder.